Mitigation in the Scientific Discourse - Abuzyarova, Darya; Takhtarova, Svetlana (Journal of History Culture and Art Research, 2018)
The article is devoted to the study of mitigation strategies and tactics in scientific discourse on the material of English, German and Russian languages. Objectivity, accuracy, consistency and clarity of presentation are traditionally distinguished as the main style-forming factors of scientific discursive practice focused on scientific knowledge. At the same time, the anthropocentrism of modern linguistic science naturally led to the inclusion in the focus of research interest of the subjective components of the scientific discourse, in which the personality of the addressee of the scientific text is reflected and to which the category of mitigation can be properly attributed. The strategy of assertive mitigation is realized in the scientific text through ritualized tactics of deictic depersonalization and modalization. These tactics reflect the interaction of two tendencies - the subjective (the author's desire to show the scientific significance of his personal contribution to scientific research, or, on the contrary, to preserve the "face" by softening the categoricity of the presentation) and objective (the desire to present only facts and strong evidence). The paper proves that the assertive mitigation strategy realized in the analyzed languages by ritualized tactics of depersonalization and modalization plays an important role in scientific discourse and serves, in the final analysis, to preserve the "face" of the addressee of the scientific text.